Is It Worth It? Perbandingan Pencatatan Inventori Pembukuan Manual dan Pembukuan Digital - Richard Riadidana; Yustinus Eko Soelistio (Universitas Multimedia Nusantara, 2014)
Green Computing is a computational resources that maximize energy efficiency and prolong the use of a device that is used , minimizing the use of paper or a book , and the electrical energy that is used every day . This paper explore the possibility to compare the cost and searching speed using Green Computing definition approach in an inventory system between using human labor, Microsoft Excel, and Inflow Inventory application. The comparison includes the data rate cost from local electricity company (PLN) and 450 samples of data. The result shows that the larger cost is incurred by using applications than using human labor. However, using applications can conclude to faster searching process than using human labor. Index Terms - Green computing, power efficiency, time efficiency